Padepokan Silat Tauhid Indonesia as mind body exercise and Bio-energy Medicines - Mustofa Muhammad (Jurnal Medika Hutama, 2020)
Silat Tauhid Indonesia is a healing/martial art adopting from hija'iyah form for stretching movement, implemented in breathing and dzikr exercise. Silat Tauhid Indonesia train breathing and dzikr for pnysical and psychosocial as well as mental health. Similar with Qigong practice, Silat Tauhid Indonesia consists primarily of internaly energy activating and developing mind, physics, awareness, sense of feeling and focus of human energy entity to heal it self and health care, as well as Bioenergy cultivation for healing. Silat Tauhid Indonesia use term Nur Alif for Bio-energy form. Bio-energy forms such as electricity, magnetic force and bio-field radiation. The increased strength if body bio-field energy through Silat Tauhid Indonesia practice provide benefit in restoring the functions of the body and in addressing the miscommunications between the internal organs, tissues, and cells, thereby preventing and healing diseases and promoting the health and quality of practitioners lives. In concise, this traditional martial art can be a future solution of health care system for individual or wider range scope.